Koordinasi Lampu Lalu Lintas Antar Simpang Pada Ruas Jalan Pemuda Jakarta Timur - Laksmini, Ni Nyoman Triana (Warta Penelitian Perhubungan, 2011)
Traffic jams that frequently occur in the Jakarta city require more serious handling of the involved parties. Traffic management arrangements are needed to improoe traffic conditions which exist today. Pemuda Street is one of the main roads in the East Jakarta Rawamangun. Transportation problems that exist today in these streets is a traffic jam caused by high traffic volume. Intersection coordination setting is the one way to reduce the level of congestion that occurs, so that during the expected congestion that occurs on these roads can be tackled. From the analysis results the queue and delay is high enough for the three intersections on Pemuda Street. Tiierefore planning of the ne--w cycle time coordination of traffic lights the same for the intersection to reduce delays and queues that occur at the intersection.Keywords: congestion, intersection coordination, reduction